STUDI KOMPARATIF KOMUNIKASI BISNIS PADA WIRAUSAHA PRIA DAN WANITA - Carin Anggun Tyas; Rauly Sijabat (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
The development of technology, globalization, and gender equality, has led women to enter various fields of work that were previously identical to those carried out by men, including entrepreneurs. However, the differences in the characteristics of men and women have implications for the way men and women entrepreneurs run their businesses. Based on these assumptions, this study was conducted to determine whether or not there are differences in business communication run by male and female entrepreneurs in managing their businesses. The research was conducted on male and female entrepreneurs or business owners in the city of Semarang. The results of the study indicate that there are differences in business communication run by male and female entrepreneurs. Where women have business communications that contain more complete messages, use short words and sentences that are carefully selected, delivered clearly, politely, and with full accuracy to the audience (consumers or business partners).